Technology of neutralization of sump at municipal solid waste landfill - Михайленко, Валерия Валериевна; Капустин, Алексей Евгеньевич (Eastern-European Journal of Enterprise Technologies, 2013)
The paper deals with studying the process of neutralization of contaminated filtrate, accumulated in a sump at municipal solid waste landfill. The main polluting components are phenols and ferrous ions. The proposed neutralization method consists of four stages and involves alignment of the sump bottom, filling the neutralizing layer, filling the absorbent layer, filling the pressing layer. In the process of water purification, its components are under control. Calcium oxide and slag are used as neutralizing mixture, and layered double hydroxides - as sorbent. The mixture is put alternatively, 1 cm of mixture by 1 cm of slag. For implementation of the neutralization method and precipitation of required amount of iron, 86.8 tons of calcium oxide and 347.1 tons of slag are needed. The total amount of layered double hydroxides, required for complete adsorption of phenols, constitutes 70 tons.